Face Captcha (International Journal of Engineering and Computer Science, 2017)
Now a day’s use of smart phone increases tremendously. User gives the priority to the touch screen mobile or tablets which is based on touch screen technology. Security level in these devices is not much as compare to the desktop computer. Today user uses the touch screen devices for online transaction. At this point issue of security is created, which is most important from user point of view. There is need of very effective online security. For that purpose CAPTCHA is used at start of any application to determine whether or not the user is human. CAPTCHA is abbreviation for Completely Automated Public Turing Test to Tell Computer and Human are Apart. This is sure option for the online transaction. It is helpful to reduce crime in online shopping or any else. It is used to prevent the automated attacks in that user have to perform task that are easy for human but challenging for computers. Actually it increases the one level of security. Hence to provide advanced security we providing new version of image based CAPTCHA called as Face CAPTCHA. It has 0 percent attack rate.